2019
DOI: 10.21203/rs.2.13255/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Palliative care training addressed to hospital healthcare professionals by palliative care specialists: a mixed-method evaluation

Abstract: Background: Despite the great advances in the concept of palliative care (PC) and its benefits, its application seems to be delayed, leaving unfulfilled the many needs of patients and family members. One way to overcome this difficulty could be to develop a new training programme by palliative care specialists to improve PC primary skills in healthcare professionals. The aim of this study was to evaluate the training's impact on trainees within a hospital setting using Kirkpatrick’s and Moore's models. Methods… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…HCP perception of the causes of inequities in access to KTWL may help ESKD subjects be registered on the list regardless of their age, sex or socioeconomic status. Education sessions dedicated to HCP could limit their misconceptions, in support of this it has been shown that training programs for HCP improve the perceptions and skills of the HCP in palliative care [14]. Among the factors of limited access to the KTWL, age is the one most well perceived by the nephrology trainees; nevertheless, a significant proportion of trainees did not notice that age was a cause of disparities in the patient's care.…”
Section: Discussionmentioning
confidence: 97%
“…HCP perception of the causes of inequities in access to KTWL may help ESKD subjects be registered on the list regardless of their age, sex or socioeconomic status. Education sessions dedicated to HCP could limit their misconceptions, in support of this it has been shown that training programs for HCP improve the perceptions and skills of the HCP in palliative care [14]. Among the factors of limited access to the KTWL, age is the one most well perceived by the nephrology trainees; nevertheless, a significant proportion of trainees did not notice that age was a cause of disparities in the patient's care.…”
Section: Discussionmentioning
confidence: 97%
“…We implemented a pre-post evaluation [32,33] of the training after adopting a specific methodology, which led us to describe the development of new knowledge, new awareness and changes in both performance and competence [34]. On the contrary, most of the training programmes described by literature have been evaluated only in terms of participants' perception and satisfaction [5,12,13].…”
Section: Discussionmentioning
confidence: 99%